2017
DOI: 10.1016/j.virol.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

ATM supports gammaherpesvirus replication by attenuating type I interferon pathway

Abstract: Ataxia-Telangiectasia mutated (ATM) kinase participates in multiple networks, including DNA damage response, oxidative stress, and mitophagy. ATM also supports replication of diverse DNA and RNA viruses. Gammaherpesviruses are prevalent cancer-associated viruses that benefit from ATM expression during replication. This proviral role of ATM had been ascribed to its signaling within the DNA damage response network; other functions of ATM have not been considered. In this study increased type I interferon (IFN) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
4
1
Order By: Relevance
“…Interestingly, MHV68 infection of primary macrophages failed to alter low levels of endogenous RT activity at both high (Fig. 1A) and low multiplicity of infection (Darrah et al, 2017), in contrast to published HCMV studies.…”
Section: Resultscontrasting
confidence: 71%
“…Interestingly, MHV68 infection of primary macrophages failed to alter low levels of endogenous RT activity at both high (Fig. 1A) and low multiplicity of infection (Darrah et al, 2017), in contrast to published HCMV studies.…”
Section: Resultscontrasting
confidence: 71%
“…We showed that ataxia telangiectasia mutated (ATM) kinase was required to amplify serine 139 phosphorylation of H2AX by MHV68 orf36 and that ATM expression facilitated replication of wild-type but not orf36-deficient MHV68 in primary macrophages (39). This proviral effect of ATM expression is entirely due to the ability of ATM to attenuate type I IFN signaling and not to its role in the DNA damage response (47). Importantly, germinal center responses were equivalently induced in control and ATM Ϫ/Ϫ mice (data not shown), indicating that activation of ATM by orf36 is not involved in the phenotypes observed in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…However, the mechanism remains unclear. We have recently found that ATM attenuates type I interferon (IFN) responses during MHV68 replication in primary macrophages, and it is this attenuation that fully accounts for the proviral activity of ATM during gammaherpesvirus replication in vitro (44). It is tempting to speculate that the infected-cell-intrinsic expression of ATM and subsequent attenuation of the type I IFN response also promote virus reactivation during chronic infection, a hypothesis that is being tested in ongoing studies.…”
Section: Discussionmentioning
confidence: 99%